2017
DOI: 10.18517/ijaseit.7.3.1003
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Media for In-Vitro Regeneration of Two Local Genotypes of Chili Pepper (Capsicum annuum L.) from West Sumatera

Abstract: Genetic engineering strategy in chilli peppers (Capsicum annuum L.) has been applied so far to improve its genetic capacity for instance against some important diseases. This strategy needs an established system for calli preparation as well as transformant regeneration. In most cases, this necessity is genotype dependent especially for some local genotypes. Based on this, we optimized media for calli induction, shoot and root regeneration of our three local cultivars namely Kampung, Kopay, and Trisula. Media … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…The shoot structures were generally obtained from nutrient media containing high cytokinin (3-5 mg L -1 BA) and low auxin (0.5 mg L -1 IAA). When the literature is examined, BA and IAA are the most commonly used plant growth regulators and combinations in organogenesis studies in Capsicum (Gunay and Rao, 1978;Agrawal et al, 1989;Arroyo and Revilla, 1991;Christopher and Rajam, 1996;Ramírez-Malagón and Ochoa-Alejo, 1996;Hyde and Phillips, 1996;Sanatombi and Sharma, 2006;Sanatombi and Sharma, 2008;Renfiyeni et al, 2017;Haque and Ghosh, 2018;Gammoudi et al, 2017). We observed that the shoot structures were generally obtained from nutrient media containing high cytokinin (3-5 mg L -1 BA) and low auxin (0.5 mg L -1 IAA).…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…The shoot structures were generally obtained from nutrient media containing high cytokinin (3-5 mg L -1 BA) and low auxin (0.5 mg L -1 IAA). When the literature is examined, BA and IAA are the most commonly used plant growth regulators and combinations in organogenesis studies in Capsicum (Gunay and Rao, 1978;Agrawal et al, 1989;Arroyo and Revilla, 1991;Christopher and Rajam, 1996;Ramírez-Malagón and Ochoa-Alejo, 1996;Hyde and Phillips, 1996;Sanatombi and Sharma, 2006;Sanatombi and Sharma, 2008;Renfiyeni et al, 2017;Haque and Ghosh, 2018;Gammoudi et al, 2017). We observed that the shoot structures were generally obtained from nutrient media containing high cytokinin (3-5 mg L -1 BA) and low auxin (0.5 mg L -1 IAA).…”
Section: Discussionmentioning
confidence: 91%
“…This may be due to the different Capsicum species used. Several studies have reported that IAA is an effective auxin for organogenesis studies in C. annuum L. However, the genotype effect is still an important factor in Capsicum genus (Venkataiah and Subhash, 2001;Renfiyeni et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation